Impact of Intrinsic Resistance Mechanisms on Potency of QPX7728, a New Ultrabroad-Spectrum Beta-Lactamase Inhibitor of Serine and Metallo-Beta-Lactamases in Enterobacteriaceae, Pseudomonas aeruginosa, and Acinetobacter baumannii - Lomovskaya, Olga (Antimicrob Agents Chemother, 2020)
QPX7728 is an ultrabroad-spectrum boronic acid beta-lactamase inhibitor that demonstrates inhibition of key serine and metallo-beta-lactamases at a nanomolar concentration range in biochemical assays with purified enzymes. The broad-spectrum inhibitory activity of QPX7728 observed in biochemical experiments translates into enhancement of the potency of many beta-lactams against strains of target pathogens producing beta-lactamases. The impacts of bacterial efflux and permeability on inhibitory potency were determined using isogenic panels of KPC-3-producing isogenic strains of Klebsiella pneumoniae and Pseudomonas aeruginosa and OXA-23-producing strains of Acinetobacter baumannii with various combinations of efflux and porin mutations. QPX7728 was minimally affected by multidrug resistance efflux pumps either in Enterobacteriaceae or in nonfermenters, such as P. aeruginosa or A. baumannii. Against P. aeruginosa, the potency of QPX7728 was further enhanced when the outer membrane was permeabilized. The potency of QPX7728 against P. aeruginosa was not affected by inactivation of the carbapenem porin OprD. While changes in OmpK36 (but not OmpK35) reduced the potency of QPX7728 (8- to 16-fold), QPX7728 (4 μg/ml) nevertheless completely reversed the KPC-mediated meropenem resistance in strains with porin mutations, consistent with the lesser effect of these mutations on the potency of QPX7728 compared to that of other agents. The ultrabroad-spectrum beta-lactamase inhibition profile, combined with enhancement of the activity of multiple beta-lactam antibiotics with various sensitivities to the intrinsic resistance mechanisms of efflux and permeability, indicates that QPX7728 is a useful inhibitor for use with multiple beta-lactam antibiotics.